Peruvian wart on the coast - Calero, Gonzalo (Revista Universidad de Guayaquil, 1990)
11 cases of Bartonellosis presented in the last 10 years are studied, coming from various places, located in the Paján and Chongón Colonche mountain ranges. The relatively benign nature of its lesions is highlighted, the absence of the blood phase and its contrast with the serious conditions described in previous decades and the hypothesis is raised that over time in the indicated area, a balance has been produced between agent and hosts, which has allowed Bartonellosis to no longer be serious, at least in the sector studied.